2017
DOI: 10.1186/s12871-017-0335-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in duration of action of rocuronium following decrease in hepatic blood flow during pneumoperitoneum for laparoscopic gynaecological surgery

Abstract: BackgroundA moderate insufflation pressure and deep neuromuscular blockade (NMB) have been recommended in laparoscopic surgery in consideration of the possible reduction in splanchnic perfusion due to the CO2-pneumoperitoneum. Since the liver is the major organ for rocuronium metabolism, the question of whether NMB of rocuronium would change with the variation of liver perfusion during pneumoperitoneum during laparoscopic surgery merits investigation.MethodsIn this prospective study, a total of sixty female pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…No simple tests will, unfortunately, allow an accurate estimation of liver function. Hepatic blood flow can also be important for duration of action of NMBAs, and one study found that pneumoperitoneum during laparoscopic surgery was associated with a prolonged duration of action of rocuronium 19 . An explanation might be a decrease in hepatic blood flow related to the increase in intraperitoneal pressure.…”
Section: Discussionmentioning
confidence: 99%
“…No simple tests will, unfortunately, allow an accurate estimation of liver function. Hepatic blood flow can also be important for duration of action of NMBAs, and one study found that pneumoperitoneum during laparoscopic surgery was associated with a prolonged duration of action of rocuronium 19 . An explanation might be a decrease in hepatic blood flow related to the increase in intraperitoneal pressure.…”
Section: Discussionmentioning
confidence: 99%
“…7 Several reports have demonstrated major inter-individual differences in the duration of action of rocuronium. 8e11 Advanced age, 12 female sex, 13 conditions and treatments that alter the skeletal muscle acetylcholine receptors, 14 decrease in hepatic blood flow during surgery, 15 smoking, 16 and ethnic background 17e19 can also affect the pharmacokinetics or pharmacodynamics of rocuronium.…”
Section: Editor's Key Pointsmentioning
confidence: 99%
“…Carbon dioxide (CO 2 ) is the most commonly used gas for insufflation of the abdominal cavity to provide better exposure during laparoscopic surgery ( 4 ). However, an increasing numbers of studies have reported that several physiological complications are closely associated with high intraabdominal pressure caused by CO 2 ( 5 - 7 ).…”
Section: Introductionmentioning
confidence: 99%